Challenges in the approach to Systemic Arterial Hypertension within primary care - Reis , Amanda de Borba; Mazon, Gabriela Nunes; Lima, Jéssyca Cássia de Faria Barbosa; Costa, Júlia Gabriela Ribeiro; Souza, Juliana Alves de; Vilela, Marcela Bandeira; Mendes, Mariana Carla (Seven Editora, 2024)
Primary Health Care (PHC) is the user’s first contact with the Unified Health System (SUS) and is responsible for solving the most prevalent diseases in the population, such as Arterial Hypertension (AH). This condition is described as the prevalence of blood pressure values equal to or greater than 140 mmHg systolic and 90 mmHg diastolic. There are several reasons that frame this disease as a challenge in PHC, among which are the quality of the doctor-patient relationship, low adherence to treatment and the lack of effectiveness in multidisciplinary care. When outlining a profile of the users who seek this help, it was observed that the majority are elderly females, with less than or equal to 8 years of schooling, white, retired and with economic classification C. It is concluded that, to have an adequate management of this reality, it is necessary to have an integrated work, involving not only pharmacological prescription, but also the promotion of changes in lifestyle combined with the patient’s health education to generate greater autonomy in the face of their disease. DOI:https://doi.org/10.56238/sevened2024.001-060